2008
DOI: 10.1111/j.1365-2702.2007.01970.x
|View full text |Cite
|
Sign up to set email alerts
|

Passing the audition – the appraisal of client credibility and assessment by nurses at triage

Abstract: Aim. This paper presents the findings of one aspect of a larger study aiming to build a substantive grounded theory of the process of initial assessment at triage. Background. Prioritisation at triage within emergency departments centres primarily on assessing the threat to physiological function of people presenting with health-care problems. This approach presumes that clinical reasoning strategies reside exclusively within the health-care practitioner, with the patient playing no active part in the process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…The analysis of the characteristics of the articles related to year of publication showed that 45.4% of the total number of publications were produced between 2007 and 2010 (12)(13)(14)(15)(21)(22)(23)(24)(25)28) , thus indicating an increase in the number of studies on this issue in recent years. Table 1 depicts these results.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the characteristics of the articles related to year of publication showed that 45.4% of the total number of publications were produced between 2007 and 2010 (12)(13)(14)(15)(21)(22)(23)(24)(25)28) , thus indicating an increase in the number of studies on this issue in recent years. Table 1 depicts these results.…”
Section: Resultsmentioning
confidence: 99%
“…According to Edwards and Sines (2006), nursing practices and research need to account for the patients' contribution to the decision-making process. Consequently, and based on the present results, we argue that the care and assessment of the individual patient must be lifeworld-centred also in pre-hospital emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…With an increase in experience, triage nurses' decisions became more based on intuition (Noon, 2014). Experienced nurses relied more on behavioural cues, time factors and medical, social and contextual factors to judge the patients' complaints (Edwards & Sines, 2008;Johannessen, 2016). During telephone triage, nurses have to deal with the absence of physical parameters and compensate for this lack of information, by creating a mental image of the patient and the situation from which the call is made (Edwards, 1998;Pettinari & Jessopp, 2001).…”
Section: Reasoning During Triagementioning
confidence: 99%